A Holistic Approach for Modeling and Synthesis of Image Processing Applications for Heterogeneous Computing Architectures - Hartmann, Christian; Yupatova, Anna; Reichenbach, Marc; Fey, Dietmar; German, Reinhard (Proceedings of HIS Workshop. Design, Automation & Test in Europe (DATE), 2015)
UnivIS-Import:2015-04-17:Pub.2015.tech.IMMD.IMMD3.aholis
Keywords: GRK-1773

An Integrated Model-driven Framework for Simulation, Analysis, and Testing Based on OMG Standards - Schneider, Vitali; Deitsch, Anna; German, Reinhard (10th International Conference on Performance Evaluation Methodologies and Tools, 2016)
Keywords: Test-driven Agile Simulation; Model-driven Engineering; Performance analysis; UML; Model-driven Testing

An Integrated Model-driven Framework for Simulation, Analysis, and Testing Based on OMG Standards - Schneider, Vitali; Deitsch, Anna; German, Reinhard (Proceedings of the 10th International Conference on Performance Evaluation Methodologies and Tools (ValueTools '16), 2017)
Model-driven engineering techniques are becoming increasingly popular for cost-effective and highly productive software development. Particularly, approaches and tools based on the standards provided by the Object Management Group (OMG), first of all on its famous Unified Modeling Language (UML), are already widespread throughout both the industry and the research community. Following this trend, the approach for Test-driven Agile Simulation (TAS) combines model-driven engineering, simulation, and testing techniques, based on OMG standards, to allow for advanced performance analysis and validation at early design stages. Among others, by deriving executable simulations from a system model and test specifications, this approach provides a cheap and agile technique for quantitative assessments and quality assurance of the system under design. In this paper, we present the current state of the SimTAny framework that provides a versatile, integrated, and standard-based tool chain to support the TAS approach. In particular, SimTAny facilitates the creation of model specifications, based on UML and several standardized profiles like SysML, MARTE, and UTP, the automated transformation to executable simulations, as well as testing and analysis activities. We demonstrate the main features of the SimTAny framework and illustrate the application of TAS on an example monocular vision system for the autonomous approach and landing that uses a low-budget micro aerial vehicle syste
UnivIS-Import:2017-01-09:Pub.2016.tech.IMMD.IMMD7.aninte_6
Keywords: model-driven engineering; model-driven testing; performance analysis; test-driven agile simulation; UML

Combined Simulation and Testing Based on Standard UML Models - Schneider, Vitali; Deitsch, Anna; Dulz, Winfried; German, Reinhard (Principles of Performance and Reliability Modeling and Evaluation, 2016)

How to Avoid Model Interferences for Test-driven Agile Simulation based on Standardized UML Profiles - Schneider, Vitali; Yupatova, Anna; Dulz, Winfried; German, Reinhard (Proceedings of the Symposium on Theory of Modeling and Simulation - DEVS Integrative (DEVS '14), 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.howtoa
Keywords: GRK-1773

Merging OMG Standards in a General Modeling, Transformation, and Simulation Framework - Schneider, Vitali; Yupatova, Anna; Dulz, Winfried; German, Reinhard (Proceedings of the 8th International Conference on Simulation Tools and Techniques (SIMUTools '15), 2015)
Keywords: MARTE; MOF2T; OMG; SysML; UML; UTP; model-driven engineering; model-driven testing; test-driven agile simulation

Model-Based System Design and Evaluation of Image Processing Architectures with SimTAny Framework - Deitsch, Anna; Schneider, Vitali (Measurement, Modelling and Evaluation of Computing Systems, 2018)
Becoming a ubiquitous part of a huge number of various applications, image processing algorithms and underling architectures have to meet many different requirements. Some have real-time performance constraints combined with demands on efficient implementation for limited or various hardware resources. This poses particular challenges for design, implementation, and evaluation of efficient image processing systems. In this paper, we present a model-based approach to address these issues using our framework SimTAny. Founded on the standard modeling language UML, we propose the UML Image Proccessing Language (UIPL) to facilitate expressing image processing application algorithms directly in UML, which is especially beneficial for rapid modeling. With the help of SimTAny, such design models can be simulated in order to investigate the performance of a modeled system, to determine optimal design solutions, and to validate the required properties. We extend SimTAny to enable the generation of efficient implementation code of image processing algorithms for different target architectures. The code generated is then directly integrated in the simulation environment to increase the accuracy of our performance evaluations.<br
Keywords: Model driven engineering; UML; SysML; MARTE; Image processing applications; High-level synthesis

Test-Driven Agile Simulation for Design of Image Processing Systems - Yupatova, Anna; Schneider, Vitali; Dulz, Winfried; German, Reinhard (The Sixth International Conference on Advances in System Testing and Validation Lifecycle (VALID 2014), 2014)
Image processing systems are characterized by very high computational demand caused by large amounts of data, short response times, and the complexity of image processing tasks. For these reasons, specialized hardware solutions based on multiple processing cores, complex interconnects, or custom hardware elements are used for image processing. Due to the complexity of the computational tasks, the complexity of the specialized hardware solutions is continuously increasing. Therefore, new design techniques that reduce the risk of lacks in the system design or of expensive design-to-implementation iterations are desirable. Test-driven Agile Simulation (TAS) is a generalpurpose approach that combines novel model-based simulation and testing techniques to achieve an improved overall quality for the development process. In this paper, we present an application and extension of the TAS approach for the efficient design process of image processing systems.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD7.testdr
Keywords: GRK-1773

Towards an Efficient High-Level Modeling of Heterogeneous Image Processing Systems - Deitsch, Anna; Schneider, Vitali; Kane, Jennifer; Dulz, Winfried; German, Reinhard (Proceedings of the Symposium on Theory of Modeling & Simulation - DEVS Integrative (DEVS '16), 2016)
Keywords: TAS; image processing systems; marte; model-based engineering; sysml; test-driven agile simulation; uml; utp